Code switching in ESL classrooms: A study of adult Arabic learners - Larbah, Manar Suliman; Oliver, Rhonda (English Australia, 2015)
Code switching (CS) between the first language (L1) and the target language (TL) in the second language classroom has been the focus of recent second language acquisition research. This paper reports on a study that investigated adult Arabic students' use of CS in four university classrooms in Western Australia. An analysis of the data found that the use of CS was present in second language classrooms. Further, regardless of Arabic students' proficiency level, CS fulfils important functions. Overall, access to the L1 through CS assisted the learners to develop linguistic competence in the TL and worked to benefit their language learning. Therefore, it is important that teachers understand that switching between L1 and the TL can enhance language acquisition.